Motivations and Challenges for Patent Filing by Universities: A Systematic Literature Review - Juliana Moletta; Luiz Alberto Pilatti (SAGE Open)
This study aims to identify the main motivations and challenges universities face in the patent filing process. The study employs a systematic literature review using the Methodi Ordinatio to select and rank articles. Initially, 14,559 articles were collected, which were reduced to 257 after several filtering stages. The final sample was limited to the top quartile of articles with the highest positive scores from the InOrdinatio equation to focus the analysis on the most relevant studies. Nvivo Pro 14 software was used for content analysis of these articles, identifying relevant concepts and categories related to the topic. The results highlight that patents’ motivations include revenue generation, strengthening academic reputation, technological advancement, and supporting research. However, universities face significant challenges, such as institutional barriers, financial constraints, and a need for incentives for commercialization. The study concludes that overcoming these barriers is crucial to maximizing the potential of patenting activities and enhancing the role of universities as drivers of innovation. Institutional reforms and incentive policies are essential to creating a more favorable environment for technology transfer, benefiting academia and the productive sector.